Vaccine Diplomacy as New Soft Power Effort of US in Dealing with China in Southeast Asia - Cahayani, Ica (Jurnal Ilmiah Hubungan Internasional, 2024)
The COVID-19 pandemic and developed countries' response to the crisis reveal that the landscape of global health governance is changing into a political realm. As countries around the world struggle to secure vaccines to break the COVID-19 chain, superpowers are actively distributing vaccines internationally in an act known as "vaccine diplomacy". The US and China have shown political interests in vaccine diplomacy, which can be seen from the way the two countries respond to achieve vaccine diplomacy targets, especially in strategic countries or regions such as Southeast Asia. This article explains US vaccine diplomacy in Southeast Asia which is considered a form of containing US power against China's vaccine diplomacy which first distributed vaccines in Southeast Asian countries. The US conducts vaccine diplomacy to compete with Chinese vaccines in accordance with the relative advantages of US politics by bringing up various diplomatic actions, namely the discourse on booster vaccines. This research uses the literature review method and the concepts of vaccine diplomacy and counter-strategy diplomacy. The results showed that US vaccine diplomacy is driven by political interests. The agenda of the vaccine diplomacy visit contains a discussion of invitations to stem China's power in the Indo-Pacific and South China Sea.    Keywords: US; China; Vaccine Diplomacy; Soft Power